2018
DOI: 10.1089/acm.2018.0076
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary Health Practices in a Church-Based African American Cohort

Abstract: Complementary health practices were used heavily in a church-based sample of African American adults. Poorer physical health was associated with use of complementary health practices, yet users also displayed health conscious behaviors. Given the high engagement in complementary health practices, it may be prudent to consider adapting complementary health approaches for use in wellness interventions targeting African Americans in faith-based settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Studies have indicated that there is both a gender and racial disparity in who seeks out massage therapy. (2)(3)(4) Results from the National Health Interview Survey (NHIS) which specifically asked questions about complementary and integrative health (CIH) utilization in 2002, 2007, and 2012 showed there was a widening gap in who sought these services by race/ethnicity. (3) While non-Hispanic whites were increasing usage of CIH, Hispanic adults and non-Hispanic Black adults saw a decrease in usage.…”
Section: United States Massage Therapy Patients/ Clientsmentioning
confidence: 99%
“…Studies have indicated that there is both a gender and racial disparity in who seeks out massage therapy. (2)(3)(4) Results from the National Health Interview Survey (NHIS) which specifically asked questions about complementary and integrative health (CIH) utilization in 2002, 2007, and 2012 showed there was a widening gap in who sought these services by race/ethnicity. (3) While non-Hispanic whites were increasing usage of CIH, Hispanic adults and non-Hispanic Black adults saw a decrease in usage.…”
Section: United States Massage Therapy Patients/ Clientsmentioning
confidence: 99%
“…Truly achieving improved health for all will require a tolerant and compassionate society, and with increased awareness and clarity comes the action to build the requisite systems to promote social and health equity, as well as the economic transformation needed to improve the lives of future generations [ 46 ]. A progressive increase in prescribing contemplative practices as a low- or no-cost, self-empowering tool for increasing spiritual awareness and improving health and self-reliance could help to reach low income, disenfranchised and often racial/ethnic minority communities that suffer most from societal-based stresses and high rates of treatable health disparities [ 47 , 48 , 49 , 50 ].…”
Section: The Way Forward: In What Way Might Contemplative Practicementioning
confidence: 99%
“… 12 Research indicates that African Americans find mindfulness practices to be compatible with and even enhance their spiritual practice, 10 and those who report poor physical health and health-conscious behavior also have higher mind-body practice usage, indicating that African Americans may perceive mind-body practice as a valuable tool to work toward a healthier lifestyle. 14 …”
Section: Introductionmentioning
confidence: 99%
“…12 Research indicates that African Americans find mindfulness practices to be compatible with and even enhance their spiritual practice, 10 and those who report poor physical health and health-conscious behavior also have higher mind-body practice usage, indicating that African Americans may perceive mind-body practice as a valuable tool to work toward a healthier lifestyle. 14 This review seeks to (1) aggregate the findings of the CAM interventions offered for AACS published from 2016 to 2021 and (2) evaluate the available research on the acceptability and interest in CAM interventions among AACS. Various nomenclature including African American, Black, and Black Americans were used throughout the studies included in this review and are used interchangeably for the purpose of this paper.…”
Section: Introductionmentioning
confidence: 99%